How can signaling in authentic classroom videos support reasoning on how to induce learning strategies? - Tannert, Swantje; Eitel, Alexander; Marder, Johanna; Seidel, Tina; Renkl, Alexander; Glogger-Frey, Inga (Frontiers in Education, 2023)
Classroom videos are a viable means to implement evidence-informed reasoning in teacher education in order to establish an evidence-informed teaching practice. Although learning with videos relieves pre-service teachers from acting in parallel and might reduce complexi-ty, the material still poses higher cognitive load than written text vignettes or other tradition-ally used static material. In particular, the information they deliver is transient and can, therefore, easily be missed. Signaling can guide learners’ attention to central aspects of a video, thereby reducing cognitive load and enhancing learning outcomes. In the current pro-ject, pre-service teachers acquired scientific knowledge about learning strategies and their promotion in a computer-based learning environment. We explored the effect of different arrangements of signaling in classroom video-examples on conceptual knowledge and the reasoning-component of professional vision. Therefore, we conducted a set of two studies with 100 student teachers including two signal arrangements in order to investigate how sig-naling can help learning to reason about classroom videos. In addition, we varied if partici-pants received information on the use of signals in advance (informed) or not (uninformed). We measured conceptual knowledge by asking participants what they knew about self-regulation strategies. Additionally, we assessed reasoning by asking participants to notice sequences in a video where teachers induced learning strategies, and to reason in what re-spect the observed behavior was useful to induce the strategy. Uninformed signaling did not affect the acquisition of conceptual knowledge and reasoning. Informed signaling led to sig-nificantly better conceptual knowledge than uninformed signaling. It is argued that the sig-nal-induced extraneous load exceeded the load reduction due to the signal’s selection ad-vantage in the uninformed conditions. In a third, exploratory study, nine participants were interviewed on the perception of different signals and indicated that spotlight and zoom-in signals foster processing of classroom videos.